2019
DOI: 10.1186/s12929-019-0543-8
|View full text |Cite
|
Sign up to set email alerts
|

Activation of TrkB/Akt signaling by a TrkB receptor agonist improves long-term histological and functional outcomes in experimental intracerebral hemorrhage

Abstract: Background Intracerebral hemorrhage (ICH) induces a complex sequence of apoptotic cascades that contribute to secondary neuronal damage. Tropomyosin-related kinase receptor B (TrkB) signaling plays a crucial role in promoting neuronal survival following brain damage. Methods The present study investigated the protective effects and underlying mechanisms of TrkB activation by the specific TrkB agonist, 7,8-dihydroxyflavone (7,8-DHF), in a model of collagenase-induced ICH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…Various forms of cell death have been identified after ICH, including apoptosis, necrosis, and autophagy in humans and experimental animals, and autophagic cell death in animal models [31][32][33]. Although inhibiting apoptosis, necrosis, and autophagy can improve outcomes in animals subjected to experimental ICH, no successful clinical trials using cell-death inhibitor monotherapy have been reported [34][35][36]. These facts suggest that multiple forms of cell death other than those mentioned above may occur after ICH and contribute collectively to neuronal death.…”
Section: Discussionmentioning
confidence: 99%
“…Various forms of cell death have been identified after ICH, including apoptosis, necrosis, and autophagy in humans and experimental animals, and autophagic cell death in animal models [31][32][33]. Although inhibiting apoptosis, necrosis, and autophagy can improve outcomes in animals subjected to experimental ICH, no successful clinical trials using cell-death inhibitor monotherapy have been reported [34][35][36]. These facts suggest that multiple forms of cell death other than those mentioned above may occur after ICH and contribute collectively to neuronal death.…”
Section: Discussionmentioning
confidence: 99%
“…TrkB is a receptor of BDNF that plays a role in stimulating neuronal survival, morphogenesis, and plasticity [44], and DHF upregulates TrkB phosphorylation via the Akt pathway [45]. The PI3K/Akt signaling pathway protects against apoptosis and promotes neuronal survival [45]. DHF activates the TrkB receptor and the PI3K/AKT and MAPK pathway in hippocampal neurons [46].…”
Section: Discussionmentioning
confidence: 99%
“…(Sivandzade et al, 2019;Hannan et al, 2020a). Inappropriate levels of antiapoptotic proteins [e.g., Bcl-2 (B-cell lymphoma 2)] and proapoptotic proteins [e.g., Bax (Bcl-2-associated X protein)] contribute to mitochondrial dysfunction and OSinduced apoptosis (Wu et al, 2019). In addition, the reestablishment of blood supply immediately after ischemia exposes brain tissue to excess oxygen, which exacerbates ROS production, which, in turn, induces further OS-associated injury, lipid peroxidation, protein oxidation, and intracellular DNA damage (Kishimoto et al, 2019;Sivandzade et al, 2019).…”
Section: Ischemic Strokementioning
confidence: 99%
“…BDNF binds TrkB and helps maintain neuronal survival and synaptic plasticity by activating canonical signaling pathways, that is, the PI3K/Akt pathway, the mitogen-activated protein kinase (MAPK) pathway, and the phospholipase C-γ (PLCγ) pathway (Kowiański et al, 2018). The PI3K/Akt signaling pathway is the major TrkB-mediated survival pathway that promotes neuronal survival and protects against apoptosis (Wu et al, 2019). Activated Akt also controls cell survival by maintaining a balance between pro-apoptotic and anti-apoptotic proteins (Sussman, 2009).…”
Section: Cell Survival System: the Trkb Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation